Original paper Can impedance cardiography be routinely applied in patients with sepsis and severe sepsis? - Piechota, Mariusz; Irzmański, Robert; Banach, Maciej; Barylski, Marcin; Ostrowski, Stanisław; Kowalski, Jan; Pawlicki, Lucjan (Archives of Medical Science, 2006)
Introduction: In the European Union only, about 146 000 patients die due to sepsis per year. Impedance cardiography (ICG) is a totally non-invasive and thus devoid of the risk of the above complications method of monitoring numerous hemodynamic parameters. The method recommended for routine application in patients with sepsis and severe sepsis should be precise, repeatable and possible to use in every case. The objective of this study was to determine the quality of the obtained impedance cardiography (ICG) signal and the value of thoracic fluid content (TFC) in patients with sepsis and severe sepsis. Material and methods: It was a prospective study. The study was performed in the Department of Anaesthesiology and Intensive Care Unit, Medical University Hospital, in the group of 20 patients with sepsis and severe sepsis. In total 128 ICG measurements (NICCOMO) were performed in all patients. Each time the level of ICG signal (in %) was determined and several hemodynamic parameters were measured including TFC. Results: The quality of ICG was ≥70% in 53.91% of the measurements, ≥30% in 88.28% of the measurements. In 11.72% of the measurements the signal quality was 65kΩ -1 in six measurements (4.69%). The mortality in the studied group was 30%. Conclusions: In conclusion the level of the obtained ICG signal and the measured TFC values in patients with sepsis and severe sepsis allow to apply ICG routinely in this group of patients.